Optimizing the Blood Donation App with Gamification Using User-Centered Design - Sari, Rida Purnama; Fatudin, Arif; Saputro, Rujianto Eko; Arifudin, Dani (Politeknik Ganesha Medan, 2024)
In today's digital era, motivating the younger generation to participate in routine voluntary blood donations is a significant challenge in the health sector. This research aimed to develop a gamified application called Gamified Blood Donation (G-BlooD), designed using the User Centered Design methodology. This application integrates gamification into the blood donation process, with features including donor location information, available blood stock data, and individual donation history. Using gamification elements such as challenges, ranking boards, and emblems enhanced user interactivity and motivation. Evaluation of G-BlooD demonstrated its effectiveness in achieving this goal; it scored 75 (Grade B) on the System Usability Scale (SUS), indicating good usability, while an average total index calculation from all responses on the Likert scale of 84.125% underscored its success in motivating younger generations towards regular blood donations. These results suggest combining digital technology with gamification can encourage recurring voluntary blood donation among younger generations. This research opens avenues for further exploration into leveraging digital technology to address other public health concerns.